2011
DOI: 10.3390/molecules16043232
|View full text |Cite
|
Sign up to set email alerts
|

Selenol Protecting Groups in Organic Chemistry: Special Emphasis on Selenocysteine Se-Protection in Solid Phase Peptide Synthesis

Abstract: The appearance of selenium in organic synthesis is relatively rare, and thus examples in the literature pertaining to the masking of its considerable reactivity are similarly uncommon. Greene's Protecting Groups in Organic Synthesis, the standard reference for the state of the art in this arena, offers no entries for selenium protective methodology, in stark comparison to its mention of the great variety of protecting groups germane to its chalcogen cousin sulfur. This scarcity of Se-protection methods makes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…(550) The half-life of this adduct was 4–8 h, and reversal required both GSH and thioredoxin 1. (551) Given that selenocysteine-carbon bonds are weaker than carbon-sulfur bonds, the carbon selenium bond is likely a better acceptor of electrons through negative hyperconjugation,(552) and that SeH is more acidic than SH,(553) it is likely that Michael adducts to protein-selenocysteine are shorter lived than protein-cysteine, assuming there are no cross links/additional protein interactions.…”
Section: Physicochemical Properties Of Biological Res and Ros And mentioning
confidence: 99%
“…(550) The half-life of this adduct was 4–8 h, and reversal required both GSH and thioredoxin 1. (551) Given that selenocysteine-carbon bonds are weaker than carbon-sulfur bonds, the carbon selenium bond is likely a better acceptor of electrons through negative hyperconjugation,(552) and that SeH is more acidic than SH,(553) it is likely that Michael adducts to protein-selenocysteine are shorter lived than protein-cysteine, assuming there are no cross links/additional protein interactions.…”
Section: Physicochemical Properties Of Biological Res and Ros And mentioning
confidence: 99%
“…Despite being weak conjugate bases, the selected pro-nucleophiles studied here and/or their analogues have been shown to undergo Michael or nucleophilic addition reactions [24,25,26]. Experimental and computational studies of Lewis acid-base adducts by Denmark et al ., indicated that a Lewis base could enhance the catalytic ability of a Lewis acid [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…, disulfides) rather than N -substituted thioamides [ 29 ]. The coupled product 14 can be viewed as a reversibly modified nucleoside, since the Se-S bond can potentially be cleaved by reduction [ 30 , 31 ]; 14 can perhaps also serve as a simplified model for a peptide oligonucleotide hybrid.…”
Section: Resultsmentioning
confidence: 99%